Simultaneous determination of the levels of deoxynivalenol, 3-acetyldeoxynivalenol, and nivalenol in grain and feed samples from South Korea using a high-performance liquid chromatography–photodiode array detector - Kim, Dong-Ho; Hong, Sung-Yong; Jeon, Mi-Hyeon; An, Jae-Min; Kim, Sung-Youn; Kim, Hyo-Young; Yoon, Bo Ryun; Chung, Soo Hyun (Applied biological chemistry, 2016)
An HPLC method combined with immunoaffinity clean-up was developed for the simultaneous analysis of deoxynivalenol (DON), nivalenol (NIV), and 3-acetyldeoxynivalenol (3AcDON) in grains and feeds. The limits of quantification of the method for DON, 3AcDON, and NIV were 11.0, 27.6, and 13.5 ng/g, respectively. HPLC analyses of 300 samples of grains and feeds collected in South Korea showed that the incidence of DON and NIV in corn was 22.5 and 7.5%, while that in rice was 4.0 and 54.0%, respectively. The incidence of DON and NIV in mixed grain powder was 62.0 and 24.0%, respectively. Our study also showed that animal feeds were mainly contaminated with DON (98.1%) in the range of 32.8–950.25 ng/g with the mean concentration of 353.32 ng/g. The levels of DON in grains did not exceed the maximum allowable limit (1 mg/kg) set by the Korean Food and Drug Administration.